2019
DOI: 10.3390/s19030599
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensors for the Detection of Heavy Metal Ions in Aqueous Media

Abstract: Due to the risks that water contamination implies for human health and environmental protection, monitoring the quality of water is a major concern of the present era. Therefore, in recent years several efforts have been dedicated to the development of fast, sensitive, and selective sensors for the detection of heavy metal ions. In particular, fluorescent sensors have gained in popularity due to their interesting features, such as high specificity, sensitivity, and reversibility. Thus, this review is devoted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(87 citation statements)
references
References 219 publications
0
86
0
Order By: Relevance
“…As a result, development of simple, rapid, and inexpensive methods for reliable on‐site detection of Cu 2+ is of great value. Fluorescent sensors in particular have attracted much interest due to their sensitivity, rapid response, and ease of use …”
Section: Introductionmentioning
confidence: 99%
“…As a result, development of simple, rapid, and inexpensive methods for reliable on‐site detection of Cu 2+ is of great value. Fluorescent sensors in particular have attracted much interest due to their sensitivity, rapid response, and ease of use …”
Section: Introductionmentioning
confidence: 99%
“…However, both techniques result in trace level detection mechanisms. De-Acha et al [34] have summarized recent advances in phosphorescence sensors, and among the reported sensors, lead and copper ions have been detected in the range of 0 to 1 × 10 −5 M. Detection of the current method is within a similar range of 0 to 1 × 10 −6 M.…”
Section: Leaching Capacity Of the Intercalated Stilbenementioning
confidence: 96%
“…In addition to their widespread use as stand-alone affinity binding reagents in analytical chemistry, aptamers have been engineered into a variety of ligand-specific biosensors, termed aptasensors [9]. Aptasensors can be designed to integrate with a variety of readout methods, such as electrochemical aptasensors [10][11][12] fluorescent aptasensors [13,14], label-free aptasensors [15,16], and aptasensors designed to interface with nucleic acid signaling cascades [17,18] or specifically for detection of targets such as pathogens [19,20] or small molecules [7,21].…”
Section: Introductionmentioning
confidence: 99%